High-intensity exercise training - too much of a good thing? - Hawley, J. A.; Bishop, D. J. (Nature Reviews Endocrinology, 2021)
Exercise training can induce robust changes in mitochondria that are beneficial for a range of metabolic health outcomes. However, a recent study suggests there might be an upper limit to the amount of high-intensity training that can be tolerated before disruptions to mitochondrial function and whole-body metabolic homeostasis occur.